Between papers and absences: Glances at memory and justice in Rafael Cuevas Molina’s novel 300 - Vargas León, Vera Beatriz (2026)
In this essay, the author analyzes violence, injustice, exile, and missing persons in Guatemala from 1950 to 1990 in the novel 300 (2011) by Guatemalan-Costa Rican writer Rafael Cuevas Molina. “300” is a number related to the police files concerning missing people in that country.